2020
DOI: 10.1111/ipd.12747
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of untreated dental caries and school performance in low‐income adolescents

Abstract: Background The possible link between dental status and school performance has been investigated. The influence of the clinical consequences of untreated dental caries in this association, however, has been minimally explored. Aim To assess the relationship between clinical consequences of untreated dental caries and school performance in adolescents, and to examine the demographics and socioeconomic status pathways by which clinical consequences of untreated dental caries is associated with school performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…On the other hand, it has been reported that neither family income nor skin color was significantly associated with school performance. 16 However, it should be noted that there is a significant discrepancy in these parameters among the different studies. For instance, some studies indicated that low socioeconomic status, low parental educational levels, and being non-white male were all significant factors associated with poor school performance.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…On the other hand, it has been reported that neither family income nor skin color was significantly associated with school performance. 16 However, it should be noted that there is a significant discrepancy in these parameters among the different studies. For instance, some studies indicated that low socioeconomic status, low parental educational levels, and being non-white male were all significant factors associated with poor school performance.…”
Section: Discussionmentioning
confidence: 97%
“…Another cross-sectional investigation conducted by Quadros et al also demonstrated that the presence of untreated dental caries was significantly correlated with an inverse association on school performance among children from low socioeconomic communities. 16 Accordingly, it has been demonstrated that untreated dental caries can substantially predict the school performance of these children. Furthermore, more deteriorated school performance and higher frequencies of untreated dental caries were also significant among males than females in this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 Moreover, DC and U-DC clinical consequences have been found to be important predictors of poor school performance in low-income adolescents. 36 There is a variable relationship between DC and nutritional status, which is mainly determined by family sociodemographic characteristics. 37 Developed countries have an unequal distribution of DC than developing countries, which could modify the risk factors associated with DC.…”
Section: Discussionmentioning
confidence: 99%